2011
DOI: 10.7778/jpkm.2011.25.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Yijungtang on Atopic Dermatitis-like Skin Lesions of NC/Nga Mouse Induced by Mite Antigen

Abstract: ObjectivesThe purpose of this study is to investigate the effects of Yijungtang(YJT) on atopic dermatitis in an in-vitro and in-vivo experiment using a RBL-2H3 mast cells and a NC/Nga atopic dermatitis mouse. MethodsIn-vitro experiment, IL-4, IL-13 mRNA expression were evaluated by a real-time PCR, IL-4, IL-13 production by ELISA and transcription factor as GATA-1, GATA-2, NF-AT1, NF-AT2, AP-1 and NF-κB by western blotting. In-vivo experiment, clinical skin score we evaluated by, hematology and Serum total IgE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
1
0
4
Order By: Relevance
“…LJT has been used to treat various symptoms such as vomiting, stomach pain, chronic gastritis, and ulceration for a long time in Eastern countries [ 1 ]. Pharmacological studies of LJT have shown antiallergic [ 2 , 3 ], antitumor, immunomodulatory [ 4 ], acute toxicity [ 5 ], and gastroprotective [ 6 ] effects. Recently, the single herbs of LJT, including Ginseng Radix Alba [ 7 ], Zingiberis Rhizoma [ 8 ], and Glycyrrhizae Radix et Rhizoma [ 9 ] were reported to have an inhibitory effects against atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…LJT has been used to treat various symptoms such as vomiting, stomach pain, chronic gastritis, and ulceration for a long time in Eastern countries [ 1 ]. Pharmacological studies of LJT have shown antiallergic [ 2 , 3 ], antitumor, immunomodulatory [ 4 ], acute toxicity [ 5 ], and gastroprotective [ 6 ] effects. Recently, the single herbs of LJT, including Ginseng Radix Alba [ 7 ], Zingiberis Rhizoma [ 8 ], and Glycyrrhizae Radix et Rhizoma [ 9 ] were reported to have an inhibitory effects against atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…이에 대 한 연구로는 氣血不足이라 보고 補氣補血 하는 十全大補湯 24) , 人參養榮湯 25) , 益氣補 血湯 26) 이 갑상선기능저하증에 미치는 영 향에 대한 연구, 腎陽虛로 변증하여 溫補 腎陽의 치법을 활용한 眞武湯 27) , 右歸飮 28) 에 대한 연구, 補陰하는 처방인 滋陰降火 . 현재까지 理中湯에 대한 연구로 는 항산화효과 13) , 알콜성 위염 보호 효과 14) , 항알러지 효과 15,16) , 진통 및 지사 효과 17) , 염증반응 억제 효과 (Fig. 3, 4).…”
Section: 간 조직의 조직병리학적 소견에 미 치는 영향unclassified
“…理中湯은 ≪傷寒論≫ 10) 에 처음 수록된 처방으로 脾胃陽虛하고 陰이 盛한 증상 의 치료에 溫中散寒시키고, 氣虛, 脾虛로 인한 증후를 補氣健脾하는데 사용하는 처방으로서 11,12) 항산화효과 13) , 알콜성 위 염 보호 효과 14) , 항알러지 효과 15,16) , 진통 및 지사 효과 17) , 염증반응 억제 효과 18 (Fig. 3).…”
unclassified
“…가 보고되었고, 이중탕을 과체중에 이용한 사례 7) , 항 알레르기 8) 및 아토피 피부염에 효과 9,10) 가 있는 것으로 알려지는 등 다방면으로 약리작용이 보고되고 있다. 이중탕은 본방(本方)뿐 아니라 다양한 질환에 가감응용(加減應用)될 수 있는 데 항암작용 11) , 대식세포의 산화분출(oxidative burst) 12,13) , 면역력 증가 14) , 비염치료 15) 에 효과가 있다고 보고되어 있다.…”
Section: 서 론 이중탕(理中湯)은 최초 한대(漢代) 장중경(張仲景)의 상한론 (傷寒論)unclassified